Penerapan Project Based Learning ‘Lacak kalorimu’ untuk Meningkatkan Hasil Belajar Operasi Bilangan Bulat dan Pecahan - Hasanah, Iswatun (Media Pendidikan Matematika, 2024)
In the 2013 curriculum it is hoped that 21st century learning can be implemented which reflects four things, namely Critical Thinking and Problem Solving, Creativity and Innovation, Communication, and Collaboration. Teachers need to open space for students to develop their creativity so that they better understand the concepts being studied by designing project-based learning. Projects produced by students are in the form of daily meal menu designs. This study aims to improve student learning outcomes in the material for arithmetic operations with integers and fractions by applying the Project Based Learning model with the project title 'Track Your Calories' in an effort to provide knowledge to students about the importance of managing a diet according to daily calorie needs while at the same time increasing students' ability to carry out operations. calculate integers and fractions, especially in calculating calories in the food you eat. This research is a classroom action research involving class VII-E with 30 students divided into two cycles. Learning with the PjBL model "Track Your Calories" has a positive impact on improving student learning outcomes as indicated by an increase in student learning completeness in each cycle, namely cycle I with a percentage of 66.67%, and an increase in cycle II, namely 86.67%. Thus, it can be concluded that the application of project based learning 'Track Your Calories' can improve learning outcomes in whole number and fraction operations.